COVID-19 Impacts Across Multiple Life Domains of Vulnerable Socio-Demographic Groups Including Migrants: A Descriptive Cross-Sectional Study - Chilunga, Felix P.; Coyer, Liza; Collard, Didier; Leenstra, Tjalling; Galenkamp, Henrike; Agyemang, Charles; Prins, Maria; Stronks, Karien (International Journal of Public Health, 2022)
Objectives: We assessed the impacts of COVID-19 on multiple life domains across socio-demographic groups in the Netherlands. Methods: After the first COVID-19 wave, we distributed online questionnaires among 13,031 participants of the multi-ethnic HELIUS cohort. Questionnaires contained questions on changes in income status, healthy behaviors, mental health, and access to non-COVID-19 health care. We then calculated differences in adjusted proportions of participants that reported negative changes across multiple life domains by migration background, age, sex, education, and occupation. Results: 4450 individuals (35%) responded, of which 4294 were included. Older populations and men seemed to be less vulnerable to negative changes in multiple life domains during the COVID-19 pandemic compared to pre-pandemic period, while populations with a migration background and lower education groups seemed to be more vulnerable to negative changes. Conclusion: Not all populations vulnerable to SARS-CoV-2 infection and mortality are also more vulnerable to COVID-19 impacts across multiple other life domains. Targeted interventions are needed in socio-demographic groups that are most impacted by COVID-19 in various life domains to prevent future disease risk.